PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS 3 SEKOLAH DASAR - Nisa', Zahrotun; Ema Zulfiani; Nova Khoirun Nisa’; Ahmad mudrikunni’am (Jurnal Tunas Pendidikan, 2026)
This study investigates the effect of implementing the Problem Based Learning of third-grade elementary school students. The objective of the research is to analyze whether there is a significant difference in student achievement before and after the implementation of the PBL model. The research used a quantitative approach with a one-group pretest-posttest design. The subjects were 21 third-grade students at SDN 1 Dersalam. Data were collected through pretest and posttest tests and analyzed using normality tests, Wilcoxon tests and N-Gain calculations. The results of the normality test showed that the pretest and posttest data were not normally distributed, so the Wilcoxon Signed Rank Test was used. The results of the analysis showed a significance value of 0.035 <0.05, which means there is a significant difference between the pretest and posttest scores. The N-Gain analysis showed an average of 0.2963 which is classified as low to moderate, with a score variation from -1.00 to 1.00. This indicates an increase in learning outcomes for most students, although not evenly distributed. This finding is supported by observations in the classroom that show an increase in active student participation in discussions and problem solving, so that the application of the PBL model remains effective in encouraging improved learning outcomes.